2019
DOI: 10.1111/1365-2745.13136
|View full text |Cite
|
Sign up to set email alerts
|

Changing disturbance‐diversity relationships in temperate ecosystems over the past 12000 years

Abstract: Disturbances such as fires and grazing have major impacts on biodiversity. While it has been suggested that species richness is highest with intermediate levels of disturbance, currently there is no consensus due to an absence of data covering large temporal and spatial scales. We developed a new method to examine disturbance‐diversity relationships (DDR) using sedimentary pollen data linked with species’ disturbance ecology. We reconstructed disturbance and diversity dynamics in the region of the European tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…This concept distinguishes between lowlands, where a diverse semi‐open landscape developed in the Middle Holocene under the influence of the Neolithic humans, and the mountains, where shady forests developed at the same time due to the relatively humid climate of this period. An altitudinal pattern was also suggested in a recent pollen‐based study of disturbance‐diversity relationship in temperate Europe (Kuneš, Abraham, & Herben, 2019; see the online supporting information to the paper). The main deviation which we identified in this study is a stronger similarity of the Carpathians to lowlands across the study area than to the Hercynian mountain ranges (see possible explanation below).…”
Section: Discussionsupporting
confidence: 72%
“…This concept distinguishes between lowlands, where a diverse semi‐open landscape developed in the Middle Holocene under the influence of the Neolithic humans, and the mountains, where shady forests developed at the same time due to the relatively humid climate of this period. An altitudinal pattern was also suggested in a recent pollen‐based study of disturbance‐diversity relationship in temperate Europe (Kuneš, Abraham, & Herben, 2019; see the online supporting information to the paper). The main deviation which we identified in this study is a stronger similarity of the Carpathians to lowlands across the study area than to the Hercynian mountain ranges (see possible explanation below).…”
Section: Discussionsupporting
confidence: 72%
“…The palynological diversity indices presented here imply that opening of the landscape, associated with early land-use and forest removal, initially led to an increase in the diversity of vegetation types across many sites, which varied regionally (Figure 4). Similar patterns identified by Kuneš et al (2019) and intensity of settlement (Kenward, 1997;Smith, 2012;Smith et al, 2010Smith et al, , 2019Smith et al, , 2020. which are governed by speciation and global extinction (McGill et al, 2015).…”
Section: Biodiversity Trends In the Holocenementioning
confidence: 63%
“…These challenges, along with taxonomic precision, the effects of sample size and pollen representation of different plant types, can result in biases in biodiversity measures (Odgaard, 1994(Odgaard, , 2001). Kuneš et al (2019) demonstrated that ecosystems were most affected by disturbances during the Early Holocene with lower level disturbance in the mid-Holocene. These shifts in disturbance were associated with pronounced changes in pollen richness.…”
Section: Periods Of Human Population Increase Are Often Associatedmentioning
confidence: 99%
“…Other claims of lack of support for the hypothesis have been due to failure to appreciate that the theory only applies to closed sysems, i.e. with a fixed species pool – gamma diversity might continue to rise with increasing disturbance in landscapes subject to invasion by exotic species (Kuneš, Abraham & Herben, ) although diversity might decrease at the local (alpha) scale if the alien species start to outcompete the indigenous flora (Milberg & Lamont, ; Fisher et al, ). This is elaborated further in Section III.5.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 99%